Metabolic reprogramming during hyperammonemia targets mitochondrial function and postmitotic senescence - Avinash Kumar; Nicole Welch; Saurabh Mishra; Annette Bellar; Rafaella Nasciemento Silva; Ling Li; Shashi Shekhar Singh; Mary Sharkoff; Alexis Kerr; Aruna Kumar Chelluboyina; Jinendiran Sekar; Amy H. Attaway; et al. (JCI Insight, 2021)
Ammonia is a cytotoxic metabolite with pleiotropic molecular and metabolic effects, including senescence induction. During dysregulated ammonia metabolism, which occurs in chronic diseases, skeletal muscle becomes a major organ for nonhepatocyte ammonia uptake. Muscle ammonia disposal occurs in mitochondria via cataplerosis of critical intermediary metabolite α-ketoglutarate, a senescence-ameliorating molecule. Untargeted and mitochondrially targeted data were analyzed by multiomics approaches. These analyses were validated experimentally to dissect the specific mitochondrial oxidative defects and functional consequences, including senescence. Responses to ammonia lowering in myotubes and in hyperammonemic portacaval anastomosis rat muscle were studied. Whole-cell transcriptomics integrated with whole-cell, mitochondrial, and tissue proteomics showed distinct temporal clusters of responses with enrichment of oxidative dysfunction and senescence-related pathways/proteins during hyperammonemia and after ammonia withdrawal. Functional and metabolic studies showed defects in electron transport chain complexes I, III, and IV; loss of supercomplex assembly; decreased ATP synthesis; increased free radical generation with oxidative modification of proteins/lipids; and senescence-associated molecular phenotype–increased β-galactosidase activity and expression of p16INK, p21, and p53. These perturbations were partially reversed by ammonia lowering. Dysregulated ammonia metabolism caused reversible mitochondrial dysfunction by transcriptional and translational perturbations in multiple pathways with a distinct skeletal muscle senescence-associated molecular phenotype.